Acute Toxicity and Ecotoxicological Risk Assessment of Three Volatile Pesticide Additives on the Earthworm—Eisenia fetida - Wenqiang Wang (MDPI AG, 2021)
Pesticide adjuvants (PAs) are important components of pesticide. Nonetheless, limited information is available regarding their toxic effects on biota in terrestrial ecosystem. In the present study, the mortality, growth inhibition ratio, and avoidance behavior of Eisenia fetida were examined to investigate the ecotoxicological effects of toluene, xylene, and trichloroethylene and further their mixture. The 24 h median lethal concentration (24 h-LC50) of the three PAs were 300.23, 1190.45, and 5332.36 mg/kg, and the 48 h-LC50 values were 221.62, 962.89, and 4522.41 mg/kg, respectively. The mixture exhibited significant synergistic effect on the E. fetida. There was significant growth inhibition on E. fetida by the tested PAs. The avoidance threshold values of E. fetida for the tested PAs were 1100 mg/kg, 250 mg/kg, 5000 mg/kg, and 25% of the mixture, respectively. The results evaluated the toxic effects of the three PAs and their mixture on E. fetida, provided a basis for ecotoxicological risk assessment of PAs in the soil ecosystem.